Congenital anterior urethral valves and diverticula: a rare disease with good prognosis - Jadaon, Abhiyutthan Singh; Champawat, Chitra; Singh, Chandra Pal (International Surgery Journal, 2025)
Congenital anterior urethral valves (AUV) are rare congenital anomalies causing lower urinary tract obstruction in children. It can occur as an isolated entity or in association with proximal diverticula. We present our experience of congenital AUV. We did a retrospective review of the medical records From September 2017 to August 2018 to analyze the clinical presentation, investigations, treatment, and outcome of 7 cases of AUV. Two patients were diagnosed as isolated AUV while five presented with associated diverticula. The age of presentation ranged from 6 months to 3 years. Weak voiding stream, swelling on the ventral aspect of the penile urethra and dribbling were the most common symptoms. Renal function was found to be deranged in two patients (28%). Hydro-ureteronephrosis was present in two boys (28%). Post-void residual volume was >20 ml (mean 55 ml) in all children. Transurethral fulguration was carried out on isolated AUV. Open resection and reconstruction were performed in patients with AUV and proximal diverticula. Surgical outcome was successful in all patients except for occurrence of surgical site infection in one patient. We conclude that in isolated AUV transurethral ablation is the treatment of choice. Primary excision and repair are preferred if a diverticulum has formed. Eventual outcomes of AUV are good if irreversible changes have not been established.